PENGARUH EXPRESS MAIL SERVICE DAN TAX TERHADAP HARGA JUAL ALBUM MUSIK KOREA DI BURSTORE (ONLINE SHOP) TAHUN 2017 - Satria Rukmana, Heru; Patimah, Eva (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2020)
This research discusses Import activities, EMS and Taxes on Import activities carried out by one of the Online Shops of Imported goods from Korea. This study aims to determine the effect of independent variabels, namely EMS and Taxes on Selling Prices of Korean Music Albums. The sample in this study amounted to 6 data from July 2017 to December 2017 in one of the Online Shop that sell music albums from Korea. The data used is secondary data with methods of collecting data and documentation, with the analysis tool used is multiple linear regression. The study resultes that EMS didn’t significantly influence the Selling Price of Korean music albums, while Taxes had a significant influence on the Selling Price of Korean music albums. Simultaneously EMS and Taxes affect the Selling Price of Korean music albums. The magnitude of the influence caused by the two independent variables is 78.9%, while the remaining 21.1% is likely to be influenced by other variables not included in this study.